ISLAMIC LAW PERSPECTIVE ON GENDER EQUALITY IN IMPROVING FAMILY WELFARE - Fasiha, Fasiha; Umar, Umar; Cahyani, Rahma; Nursafitri, Erika (Al-Qalam, 2023)
Gender equality is a global issue that can contribute to improving the country's economy. The role of women in improving family welfare is very important for economic development. Islam has provided space for women to have the right to work. This study analyzes the contribution of female farm workers to family welfare in East Luwu Regency. The contribution is in the form of increasing family income and family financial management strategies. In addition, this study analyzes the perspective of Islamic law on working wives. The method used in this study is a mixed method. Quantitative methods to measure the contribution of female farm workers to family income and qualitative methods to analyze family financial management strategies, as well as the perspective of Islamic law on working wives. The results of the study show that female farm workers greatly contribute to increasing family income. In addition, women farm workers have a good financial management strategy by implementing long-term investments in the form of cattle and children's education. The perspective of Islamic law towards working wives is based on family conditions and situations. Islam does not prohibit wives from working as long as they do not violate Islamic law